Associating executive dysfunction with behavioral and socioemotional problems in children with epilepsy. A systematic review. Issue 5 (4th July 2021) - van den Berg, Lydia; de Weerd, Al W.; Reuvekamp, Marieke H. F.; van der Meere, Jaap J.
ABSTRACT: As children with epilepsy may have a number of learning and behavioral problems, it is important that insight into the underlying neurocognitive differences in these children, which may underlie these areas of challenge is gained. Executive function (EF) problems particularly are associated with specific learning abilities as well as behavioral problems. We aim to review systematically the current status of empirical studies on the association between EF problems and behavior and socioemotional problems in children with epilepsy. After search, 26 empirical studies were identified, most of them of moderate quality. Overall, attention problems were the most reported cognitive deficit in test assessment and the most reported problem by parents. In 54% of the studies, children with epilepsy scored below average compared to controls/normative samples on different aspects of EF. Most studies reported behavior problems, which ranged from mild to severe. Forty-two percent of the studies specifically reported relationships between EF deficits and behavioral problems. In the remaining studies, below average neuropsychological functioning seemed to be accompanied by above average reported behavioral problems. The association was most pronounced for cognitive control and attention in relation to externalizing behavior problems. This cognitive control is also associated with social functioning. Relevant epilepsy variables in this relationship were early age at onset and high seizure frequency. Future research should distinguish specific aspects of EF and take age into account, as this provides more insight on the association between EF and behavior in pediatric epilepsy, which makes it possible to develop appropriate and early intervention.